Examining the benefit of graduated compression stockings in the prevention of hospital-associated venous thromboembolism in low-risk surgical patients: a multicentre cluster randomised controlled trial (PETS trial). Issue 1 (17th January 2023) - Machin, Matthew; Peerbux, Sarrah; Whittley, Sarah; Hunt, Beverley J; Everington, Tamara; Gohel, Manjit; Norrie, John; Epstein, David; Warwick, David J; Baker, Christopher; Hamady, Zaed; Smith, Sasha; et al.
Abstract : Introduction: Hospital-acquired thrombosis (HAT) is defined as any venous thromboembolism (VTE)-related event during a hospital admission or occurring up to 90 days post discharge, and is associated with significant morbidity, mortality and healthcare-associated costs. Although surgery is an established risk factor for VTE, operations with a short hospital stay (<48 hours) and that permit early ambulation are associated with a low risk of VTE. Many patients undergoing short-stay surgical procedures and who are at low risk of VTE are treated with graduated compression stockings (GCS). However, evidence for the use of GCS in VTE prevention for this cohort is poor. Methods and analysis: A multicentre, cluster randomised controlled trial which aims to determine whether GCS are superior in comparison to no GCS in the prevention of VTE for surgical patients undergoing short-stay procedures assessed to be at low risk of VTE. A total of 50 sites (21 472 participants) will be randomised to either intervention (GCS) or control (no GCS). Adult participants (18–59 years) who undergo short-stay surgical procedures and are assessed as low risk of VTE will be included in the study. Participants will provide consent to be contacted for follow-up at 7-days and 90-days postsurgical procedure. The primary outcome is the rate of symptomatic VTE, that is, deep vein thrombosis or pulmonary embolism during admission or within 90 days. Secondary outcomes include healthcare costs and changes in quality of life. The main analysis will be according to the intention-to-treat principle and will compare the rates of VTE at 90 days, measured at an individual level, using hierarchical (multilevel) logistic regression. Ethics and dissemination: Ethical approval was granted by the Camden and Kings Cross Research Ethics Committee (22/LO/0390). Findings will be published in a peer-reviewed journal and presented at national and international conferences. Trial registration number: ISRCTN13908683 .